(untitled) (Journal of Experimental and Clinical Anatomy, 2004)
I report a case of a 35-year-old woman who presented at the Casualty outpatient department with the history of having felt her spine snap while lifting a heavy table. She thereafter experienced severed back pain and weakness of her lower limbs. Two days later, she was unable to walk. There had been a previous similar episode precipitate by a fall when she was 16 weeks thereafter suffered from recurrent weakness of her limbs. She was 39 weeks pregnant and had previously had 5 children with an uneventful obstetric history.